The Effect of Providing Additional Food (PMT) Local Food on the Nutritional Status of Toddlers Age 12-59 Months in Work Area Siriwini Community Health Center - Levina Bless; Nur Al-Faida; Alfred Denius Lambey (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Background:Supplemental Feeding (PMT) is an activity of providing food in the form of safe and quality snacks along with other supporting activities by considering aspects of food quality and safety. There are two types of supplementary feeding, namely supplementary recovery feeding and supplementary counseling (PMT). Supplemental feeding (PMT) of local food is one of the strategies for handling nutritional problems in toddlers. The PMT activity needs to be accompanied by nutrition and health education for behavioral change, for example with support for breastfeeding, education and counseling on feeding, cleanliness and sanitation for families. Nutritional status is a state of the body as a result of food consumption and use of nutrients, where nutrients are needed by the body as a source of energy, growth and maintenance of body tissues, and regulators of body processes. Nutritional status is greatly influenced by nutritional intake. Objective: To determine the effect of providing local supplementary feeding (PMT) on the nutritional status of toddlers aged 12-59 months. Method: This type of research uses quantitative research using a pre-experimental design pretest-posttest research design. Results: Based on the results of the study, it was shown that a p-value of 0.41 (> 0.05) was obtained. Conclusion: Provision of Local Supplementary Food (PMT) Has No Relationship with Toddler Nutritional Status at UPTD Siriwini Health Center. Suggestion: It is expected that mothers who have toddlers pay more attention to the growth and development of toddlers.